Organizational culture of physicians on the Island of crete - Rovithis, Michalis; Linardakis, Manolis; Merkouris, Anastasios; Philalithis, Anastasios (My University, 2016)
OBJECTIVE To identify the organizational culture profile, as experienced by physicians, overall and in the various levels of health care facilities in Crete. METHOD A cross-sectional study was conducted with a sample of 75 doctors at 7 of the 14 public primary health centers (HCs), four general hospitals (GHs) and one tertiary university hospital (UH) on the island of Crete, Greece. A multistage random sampling method was applied. The Greek edition of the questionnaire Organizational Culture Inventory® (OCI®) was used to measure organizational culture. This questionnaire is based on the theoretical framework of Cooke, Rousseau and Lafferty concerning the shared behavioral expectations and normative beliefs that operate within an organization and represent its culture. Analysis of the physicians’ responses results in percentage scores of primary culture styles grouped in clusters. RESULTS The operating organizational culture that best characterizes the physicians working in the health care facilities in Crete, overall and at the various levels of health care is the Aggressive/Defensive cluster (overall: 92nd centile; physicians in primary, secondary and tertiary health care level facilities, respectively: centiles 91.75, 84.75 and 90.75). In the primary health care HCs, of the 12 culture styles the most frequently occurring behaviors (primary styles) reported by the physicians were the Oppositional, Power and Avoidance styles (98 centile). The Power culture style (95 centile) was revealed as the primary style also in the secondary health care GHs. Physicians in the tertiary UH reported that the most frequently occurring behavior (primary style) was Avoidance (98 centile). The Constructive cluster of culture styles featured low in the responses of the physicians both overall and at the level of health care facility, with the lowest scores among those employed in the primary health care HCs, and specifically for the Humanistic (5 centile) and Affiliative (10 centile) culture styles. CONCLUSIONS Physicians face challenges both at organizational level and with regard to their professional status. A shift to more constructive organizational behaviors will lead physicians, together with the other health care professionals, towards greater adaptability, enabling them to achieve more effective, qualitative performance in a rapidly changing and demanding health care environment.
Keywords: Crete; Health care services; Organizational culture; Physicians; Quality of health care